Tou Nong San Attenuates Inflammation in TNBS-IBD Model by Inhibiting NF-κB Signaling Pathway - Zhipeng Hu (Evidence-Based Complementary and Alternative Medicine, 2018)
The incidence of inflammatory bowel disease (IBD), which predominantly comprises Crohn’s disease and ulcerative colitis, is increasing worldwide. However, the treatment of IBD still faces great challenges. The involved NF-κB is the main signaling pathway in human IBD and thus is a prime target. There is abundant evidence that Tou Nong San (TNS), which is a traditional Chinese medicinal decoction used for treating sores and carbuncles, has a positive effect on the inflammation. This study investigated the effects of oral administration of TNS on colitis induced by 2,4,6-trinitrobenzenesulfonic acid (TNBS) and the underlying mechanism(s). Quality control of the major compounds in TNS was performed by high-performance liquid chromatography, and six chemical constituents were identified in aqueous extracts. TNS led to improvements in weight loss and water and food intake in rats. The macroscopic and microscopic scores of rat tissues greatly decreased. Protein and mRNA levels of proinflammatory cytokines, including interleukin-17 (IL-17), tumour necrosis factor-α, IL-1β, and IL6, involved in the NF-κB signaling pathway were greatly reduced. The results suggest that the anti-inflammatory effect of TNS is associated with the regulation of the NF-κB signaling pathway, which contributes to the network pharmacological effect of TNS on human IBD in clinical practice.